Análise de remolhamento de vareta combustível PWR utilizando a formulação aperfeiçoada de parâmetros concentrados - Pereira, Gustavo Domingos (2017)
This work develops an analytical model using the improved lumped parameter formulation with Hermite approximations to determine the behavior of fuel rods of a typical PWR reactor when being rewetted after a postulated LOCA. Firstly, the fuel rod was represented by a cylinder with uniform volumetric heat generation, with the presence of the gap and the cladding modeled by a global coefficient of convective heat transfer. Considering the constant rewetting velocity, the rewetting problem was transformed into a steady-state heat conduction problem in the reference system fixed with the rewetting front. Applying the lumped parameter formulation in the radial direction and considering the azimuthal symmetry, the mathematical model was reduced to the one-dimensional heat conduction equation in the longitudinal direction of the fuel rod. The solutions were obtained analytically for temperature distributions in the wet and dry parts, and the rewetting velocity was determined by combining the solutions at the rewetting front. The number of Peclet based on the rewetting velocity was obtained as a function of the Biot numbers and of the dimensionless of volumetric heat generation rate. The obtained solutions compared favorably with available solutions in the literature. Finally, the problem of fuel rod was modeled in two regions, the fuel and the cladding, with the presence of the gap. Analytical solutions were obtained for the temperature distributions on the two parts of the fuel rod using the lumped parameter formulation.